Pemikiran Islam Tentang Jiwa Dalam Filsafat Islam - Kamaruddin, Kamaruddin (Al-Hikmah Journal for Religious Studies, 2014)
The soul, it is so called maujud can be comprehended as the thing of physical matter which is related to human. It is invisible and unhiding. In other aspects, the soul can have specific meanings as non-material. It flows in human body as substiansial which is unrelated to others. The word of al-nafs is mentioned in Al-Qurâan which is amount about 250 times much more than the word of al-ruh. The word of al-nafs is sometimes defined as ruh and it is not on the contrary. It means that the element of soul (al-nafs) is emanated from ruh. Ruh is the core and soul is the part of ruh. The soul is immortal and will feel torture and suffering. The immortal soul which is defined by Moslem philosophy can be confronted with the truth of Al-Qurâan which is talking about the human resurrection in some ways. First, it is suggested that the philosophy of human soul is the highest level, the soul is the core of immortal soul and human body will get destruction.